2014
DOI: 10.1155/2014/123640
|View full text |Cite
|
Sign up to set email alerts
|

Stress Hormone and Reproductive System in Response to Honey Supplementation Combined with Different Jumping Exercise Intensities in Female Rats

Abstract: This study was performed to determine the effects of 8-week honey supplementation combined with different jumping exercise intensities on serum cortisol, progesterone, estradiol, and reproductive organs. Eighty-four 9-week-old female rats were divided into 7 groups: baseline controls (C0), sedentary group (C), 20 and 80 jumps per day (Ex20J, Ex80J), honey (H), and combined honey with 20 and 80 jumps per day (HEx20J, HEx80J) groups. Jumping exercise was performed at 5 days/week and honey was given at a dosage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 34 publications
(46 reference statements)
0
28
2
Order By: Relevance
“…In the present study, there was no established relationship between the cortisol and the Estradiol levels. This finding is at variance with a closely related research finding done on the Sprague dowry rats [9] where it was reported that increased serum cortisol levels during exercise led to a decrease in serum progesterone which indicated possible suppression of reproduction by increased cortisol levels-a clear indicator of physiological stress. This finding is also similar to that reported in another study where levels of oestrogen and progesterone were shown to decrease as the responsiveness to stress increased [10].…”
Section: Discussioncontrasting
confidence: 91%
“…In the present study, there was no established relationship between the cortisol and the Estradiol levels. This finding is at variance with a closely related research finding done on the Sprague dowry rats [9] where it was reported that increased serum cortisol levels during exercise led to a decrease in serum progesterone which indicated possible suppression of reproduction by increased cortisol levels-a clear indicator of physiological stress. This finding is also similar to that reported in another study where levels of oestrogen and progesterone were shown to decrease as the responsiveness to stress increased [10].…”
Section: Discussioncontrasting
confidence: 91%
“…In the present study there was no established relationship between the cortisol and the Estradiol levels. This nding is at variance with a closely related research nding done on the Sprague dowry rats [7] where it was reported that increased serum cortisol levels during exercise led to a decrease in serum progesterone which indicated possible suppression of reproduction by increased cortisol levels-a clear indicator of physiological stress. This nding is also similar to that reported in another study where levels of oestrogen and progesterone were shown to decrease as the responsiveness to stress increased [8].…”
Section: Discussioncontrasting
confidence: 87%
“…With respect to the anaerobic training, it presented higher osteogenic potential than aerobic training (swimming) since after just four weeks, it was able to significantly increase BMD with respect to the aerobic swimming training groups (ET4) and the group without training (BL), and the same occurred with concurrent training. In this way, the osteogenic effect of the water jump (anaerobic training) was demonstrated to be effective, even when combined with exercise without impact (aerobic swimming training) 18 . In addition, training with no impact was demonstrated not to be detrimental to BMD, since although it did not increase BMD, it also did not induce significant losses in the deposition of calcium in the bone, and did not detract from the osteogenic effect when combined with anaerobic jump training (concurrent group) 1,2,6 .…”
Section: Discussionmentioning
confidence: 99%